Mapping the distribution of potential octopus (Octopus sp.) fishing ground in the waters of Simeulue regency - Muhammad Arif; Afdhal Fuadi; Giovanni Oktavinanda (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Simeulue Regency has the potential for diverse and abundant marine resources; one of which is octopus (Octopus sp.). However, the problem faced by Simeulue fishermen in carrying out octopus fishing activities is that they only rely on natural phenomena or natural signs studied from generation to generation (traditional) to catch octopus. Therefore, the catch obtained is uncertain and takes a long time. The purpose of this study was to determine the number and weight of octopus catches landed in three sub-districts namely Teupah Barat, Teupah Selatan and Alafan, and then make a map of distribution of potential octopus fishing groud in the three sub-districts. The research method used in this study was a survey method by observing octopus catching units. The results showed that the total number and total weight of octopus catches in three sub-districts from the highest to the lowest were Teupah Barat, amounting to 176 heads and weighing 90,47 kg; Teupah Selatan amounting to 115 heads and weighing to 69,54 kg; and Alafan amounting to 114 heads and weighing to 46,97 kg, where the octopuses caught were all adult categories and fit to be caught. As for the potential areas for octopus fishing in the three sub-districts were as follows: Teupah Barat with 3 potential areas (points E, F and A); Teupah Selatan with 2 potential areas (points E and F); Alafan with only 1 potential point (point K).Keywords:MappingFishing groundOctopusSimeulue